Composition and population fluctuation of the spider community in a cotton field at Universidad Nacional Agraria La Molina, Lima, Peru - Cruz, Laura (2019)
In this work, the spider community was assessed during the whole phenological period of a cotton crop using two sampling techniques (direct search and pitfall traps). 2304 individuals were registered, grouped into 50 species and 18 families. The spiders were present during the whole crop’s period; positively related to its phenological development; agronomic practices, temperature and humidity were not influential in their abundance, except for harvest, which negatively influenced their population.